PELATIHAN LARI SIRKUIT HALUAN KIRI LEBIH BAIK DARIPADA HALUAN KANAN UNTUK MENINGKATKAN KELINCAHAN PEMAIN SEPAK BOLA SISWA SMK X DENPASAR - Daniel Womsiwor; I Nengah Sandi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2014)
Agility is basic movement of physic or activity of human body required to be trained exclusively. Until today, all coaches not yet find excellent type and measurement of training to enhance agility of football player, so study is performed, tried two types and measurement of training, that are, running training with left and right side circuit system to enhance agility. Training is conducted in the morning at Stadium Ngurah Rai Denpasar start from 7.30 am until 9.30 am. Duration is 6 weeks by frequency three times a week. Sample are 24 people chosen randomly simple from student grade II SMK X Denpasar comply terms. Total sample each are 12 people, then each groups are given different training, i.e. group 1 is given running training with left side circuit system and group 2 is given running training with right side circuit system. Data for agility before and after treatment. Data obtained is tested with program SPSS, each with couple T-test to know enhancement result of running of each treatment group and T-test uncouple to know better treatment in increasing agility result. Meaning limit used is 0,05 (p<0,05). Statistic test is obtained meaning increase on running training with left side circuit system (p<0,05) and running training with right side circuit system (p<0,05). Different result of agility can not meaning different (p>0,05) and after training, there are meaning differences (p<0,05). This means that running training with left side circuit system is more giving effect to increase of agility result to football player. Therefore it is expected to all coaches and sport teacher train football in order to apply left side circuit system in giving training.